Pelatihan Pembuatan Desain Sederhana Pada Wali Murid Pelaku Usaha Rumahan di TK Jauharotul Huda - Maimunah Maimunah; Nurmala Dewi Qadarsih; Finata Rastic Andrari (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The purpose of this community service activity is to help the guardians of the students of Jauharotul Huda Kindergarten, home-based entrepreneurs, so that they can develop skills and indirectly improve the family's economy, especially by using the Canva application. To achieve this goal, the training method for making simple designs is training. directly. The target of this community service activity is the guardians of students of home-based businesses at Jauharotul Huda Kindergarten with a total of 9 trainees. The training is carried out with three stages of activities consisting of observation, training implementation, as well as evaluation and monitoring. During the observation stage, an analysis of the problems and needs of the parents of home-based businesses was carried out to create simple designs using the Canva application. At the implementation stage of the activity, material exposure and direct practice were given. In the evaluation and monitoring phase, direct evaluation and monitoring is carried out to see the abilities that have been achieved by the guardians of students at Jauharotul Huda Kindergarten in making simple designs with the Canva application. Through this simple design training, it is hoped that it can improve the skills and economy of the families of the guardians of students who do home-based businesses at Jauharotul Huda Kindergarten